A prototype tool to assess the functional quality of e-commerce websites - Maskat, Ruhaila; Zulzalil, Hazura; Abbas, Wan Faezah (2006)
E-Commerce website is the new marketing and sales method to reach new customers.By overcoming the geographical constraint, e-commerce website allows users to perform purchasing activities without being physically present.Though many e-commerce websites have achieved great success, many have also failed.Their failures are mainly due to the absence of quality.This study presents a prototype software tool that could assist in assessing the functional quality of e-commerce websites in an automatic manner.Unlike the currently available methods of evaluation, this tool does not necessitate the assessment of e-commerce websites by a human expert.On the other hand, the tool performs a scanning activity to allocate the existence of e-commerce characteristics.Adopting the quality model by Stefani and Xenos (2001), six different e-commerce characteristics were selected from the functional factor of the model.Three other factors identified by the model are usability, reliability and efficiency, which are not within the scope of this project.Three major script languages have been sited to be regularly used in e-commerce website development.They are JavaServer Pages (JSP) from Sun Microsystems, ASP from Microsoft and PHP an open source language.Though they share the same functionalities, they differ considerably in syntax.Therefore, this project has focused on evaluating e-commerce websites, which were built using JavaServer Pages (JSP).The objective of this paper is to develop a prototype tool capable of evaluating JSP-based e-commerce website based on the characteristics chosen.The tool is competent to perform the data collection through fully automatic means and finally generates result of evaluation into XML format.